What to eat when you're pregnant eaudiobook A week-by-week guide to support your health and your baby's development. - Avena, PhD, Nicole M. (Tantor Media, 2019)
An approachable guide to what to eat—as opposed to what to avoid—while pregnant and nursing, to support the mother's health and the baby's development during each stage of pregnancy. New research suggests that the foods you eat during pregnancy can have lasting effects on your baby's brain development and behavior, as well as your waistline. Drawing from the fields of medicine, nutrition, and psychology, this easy-to-follow guide gives you a clear understanding of what your body really needs and how certain foods contribute to the development of a healthy and happy baby.